Osmotic consolidation of an expansive soil - Li, Lingyan (2018)
The expansive soil has a potential for large volume change due to pore water content variation. Osmotic consolidation occurs, when the expansive soil is inundated in salt solution. This project aims to investigate the effect of osmotic consolidation on an expansive soil by making the comparison between osmotic stress and mechanical stress. The oedometer apparatus was used to carry out the consolidation test with load increments. Two kaolin-bentonite mixtures were used: KB30 (30% bentonite content) and KB10 (10% bentonite content). Three saturated salt solutions with different concentration were used: K2SO4 solution, KCl solution and NaCl solution. The results show that the effect of osmotic consolidation depends on the initial void ratio of soil, concentration of salt solution, as well as the double diffuse layer effect.